Impact of Doubling Farmers’ Income on Area, Production and Productivity of Pulses in India: A Recent Study - S. B. Ramya Lakshmi; Priyanka Patra; K. C. Gummagolmath (Current Approaches in Science and Technology Research Vol. 1, 2021)
India is the largest producer and consumer of pulses in the world contributing around 25-28% of the total global production. Pulses are considered as the climate-smart crops which helps the small farmers in arid and semi-arid regions of the world, withstand weather variability, require less water, enrich the soil and are packed with nutrition. The increasing demand and supply gap of pulses has led to an increasing trend in their import by India. In view of this gap, one of the strategies for “Doubling Farmers’ Income by 2022” was to enhance area, production and productivity of pulses in India by incentivizing the farmers with right price. Hence an attempt has been made in this study to analyze the growth of pulses over a period of time i.e. from 1980-81 to 2017-18 in India using secondary data. The average annual growth rates and percentages were used as tools to carry out analysis. The results revealed that area, production and productivity of total pulses was positive but indicating a slow growth of 1.36 per cent, 3.29 per cent and 2.04 per cent respectively per annum. Due to steep hike in Minimum Support Price (MSP) during 2015-16, it was noticed that area, production and yield have recorded higher growth than previous years. The percentage change in area, production and productivity for major pulses during three periods indicated that there was a marginal increase in area and production of gram in major producing states and the same trend was noticed in red gram and black gram. It was also observed that in some of the states the growth in period- III for major pulses was higher compared to period-II. Policy implications or lessons learned are missing!